1987
DOI: 10.1002/tera.1420350115
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity of sex steroidal hormone combinations in nonhuman primates: I. Norethisterone acetate + ethinylestradiol and progesterone + estradiol benzoate (Macaca mulatta, Macaca fascicularis, and Papio cynocephalus)

Abstract: Two sex steroid hormone combinations which have been used clinically as tests for detection of early pregnancy were examined for embryotoxic effects in macaques and baboons. Norethisterone acetate and ethinyl estradiol (NEA + EE) were orally administered to rhesus and cynomolgus monkeys and baboons at dosages ranging from one to 1,000 times the human dose equivalent (HDE) during days 20-50 of pregnancy. Progesterone and estradiol benzoate (P + EB) were delivered by two to six intramuscular injections to rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Repeat studies with ABT-874 in cynomolgus monkeys showed that the clitoral protrusion represented an insignificant developmental delay, rather than a frank malformation because this was not evident at term. Clitoral enlargement in cynomolgus monkeys had previously been reported for sex steroid hormone combinations (Hendrickx et al, 1987). Therefore, for the second embryofetal development study in which ustekinumab was administered by subcutaneous injection, sex steroids were included as part of the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat studies with ABT-874 in cynomolgus monkeys showed that the clitoral protrusion represented an insignificant developmental delay, rather than a frank malformation because this was not evident at term. Clitoral enlargement in cynomolgus monkeys had previously been reported for sex steroid hormone combinations (Hendrickx et al, 1987). Therefore, for the second embryofetal development study in which ustekinumab was administered by subcutaneous injection, sex steroids were included as part of the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Boys with Tanner stage 2 development or higher, buried penis, chordee without hypospadias, imperforate anus, exposure to corticosteroids or growth hormone, or known syndromes were excluded. Collected data Hendrickx et al [29] Cynomolgus monkey included aggregate size distribution (AASD) and potential aggregate size distribution (PASD) [4], age, height, weight, race, and urologic diagnoses. To account for prematurity, age at measurement was adjusted based on gestational age at birth.…”
Section: Possible Associations Among Anogenital Distance Endocrine Dmentioning
confidence: 99%
“…Epidemiologic and animal studies have found no significant relationship between clinically administered progestational drugs and congenital malformations [33,34]. However, in one study, embryonic deaths occurred in pregnant rhesus monkeys treated with intramuscular injections of 17P [35].…”
Section: Currently Role Of Progeterone In Prematurity Preventionmentioning
confidence: 95%